2017
DOI: 10.3390/ijerph14040377
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Exercise in Natural Environments? Norwegian Adults’ Motives for Nature-, Gym-, and Sports-Based Exercise

Abstract: Exercise in natural environments (“green exercise”) confers numerous health benefits, but little is known about why people engage in green exercise. This study examined the importance of nature experiences as a motive for physical activity and the motivational profile of people who engage in green exercise compared to gym- and sports-based exercise. Physical activity motives and typical times spent in different domains of physical activity were reported by 2168 Norwegian adults in a survey. Experiencing nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 41 publications
9
80
1
1
Order By: Relevance
“…Typical informal and flexible sports settings are commercial health centres and gyms, informal groups and individual participation in the public space, all of which make participants less dependent on formal structures such as membership obligations, opening hours and the availability of specific sports facilities [ 6 , 7 ]. Informal, unorganized and individual types of sports such as running, cycling, and working out in the gym have become increasingly popular, which has resulted in a greater variety of geographical locations used for sports activities, including public spaces and natural environments [ 3 , 8 , 9 ]. According to Borgers et al [ 6 ], these changes in sports participation can be seen as an issue of institutional change, which is related to processes of cultural and societal change and changing values, habits and attitudes of sports participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical informal and flexible sports settings are commercial health centres and gyms, informal groups and individual participation in the public space, all of which make participants less dependent on formal structures such as membership obligations, opening hours and the availability of specific sports facilities [ 6 , 7 ]. Informal, unorganized and individual types of sports such as running, cycling, and working out in the gym have become increasingly popular, which has resulted in a greater variety of geographical locations used for sports activities, including public spaces and natural environments [ 3 , 8 , 9 ]. According to Borgers et al [ 6 ], these changes in sports participation can be seen as an issue of institutional change, which is related to processes of cultural and societal change and changing values, habits and attitudes of sports participants.…”
Section: Introductionmentioning
confidence: 99%
“…For participants who participate in gym or outdoor settings under the guidance of a fitness instructor, health management and skill development goals were most important, followed by physique enhancement and social affiliation [ 20 ]. A Norwegian study showed that adults who exercise in natural environments reported stronger motives concerning convenience (e.g., easy accessibility in terms of time, location, money and ‘practising at their own pace’) and experiencing nature than did gym or organized sports participants, who reported stronger motives for improving physical health and sociability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, in addition to essential planting plans, hospital planners and landscape architects should establish opportunities for people to conduct exercise because, in our study, the landscape features that facilitate physical activities effectively encourage more visits in general. Designers can consider including features that assist both mild and vigorous levels of exercise for people in various physiological states in hospital [ 49 ]. Specifically, in the areas planning to serve people who work in, and reside near, hospitals, designers can consider features associated with middle- to vigorous levels of physical activities such as sports facilities and fitness equipment, while the areas serving patients can be installed with features that support low-impact and moderate activities with standards of universal design to accommodate friendly access and smooth movements.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have explored the role of individuals' thoughts and feelings on green exercise behaviours (Calogiuri & Elliott, 2017;Curry, Crone, James, & Gidlow, 2011;Groshong, Stanis, Kaczynski, Hipp, & Besenyi, 2017;Loureiro et al, 2014). For example, Calogiuri and Elliott (2017) found that for Norwegian adults, experiencing nature was the second-most important motive for exercise, exceeded only by convenience. Furthermore, individuals who have a higher connectedness with nature tend to spend more time in nature, and subsequently do more green exercise (Flowers, Freeman, & Gladwell, 2016).…”
Section: Accepted Manuscript Expementioning
confidence: 99%